3x-y+2z=1

2x+3y+3z=4

x+y-4z=-9

Printable View

- July 19th 2005, 02:47 PMAshiebug3Solve
3x-y+2z=1

2x+3y+3z=4

x+y-4z=-9 - July 19th 2005, 11:26 PMrgep
You need to systematically eliminate one variable, say x, from the equations by subtracting a suitable multiple of one equation from all the others. Equation (3) begins with x so we'll use that.

3x-y+2z=1 ... (1)

2x+3y+3z=4 ... (2)

x+y-4z=-9 ... (3)

-4y + 14z = 28 ... (1)-3*(3) = (4)

y + 11z = 22 ... (2)-2*(3) = (5)

Now solve (4) and (5) for y and z and substitute the values for y and z into (3) to get x. Don't forget to check your answer!